2020
DOI: 10.3390/rs12152414
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Regional Soil Moisture Distribution Based on NDVI and Land Surface Temperature Time Series Data in the Upstream of the Heihe River Watershed, Northwest China

Abstract: Temporal and spatial variability of soil moisture has an important impact on hydrological processes in mountainous areas. Understanding such variability requires soil moisture datasets at multiple temporal and spatial scales. Remote sensing is a very effective method to obtain surface (~5 cm depth) soil moisture at the regional scale but cannot directly measure soil moisture at deep soil layers (>5 cm depth) currently. This study chose the upstream of the Heihe River Watershed in the Qilian Mountain Ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(63 reference statements)
2
13
0
Order By: Relevance
“…Retrieving SSM using remote sensing technology has been investigated for more than 30 years. Among the remote sensing methods, most optical methods estimate SSM by using the spectral reflectance indices, which are easy to implement but can be easily affected by weather [8]. In thermal infrared methods, SSM is mainly estimated from thermal inertia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving SSM using remote sensing technology has been investigated for more than 30 years. Among the remote sensing methods, most optical methods estimate SSM by using the spectral reflectance indices, which are easy to implement but can be easily affected by weather [8]. In thermal infrared methods, SSM is mainly estimated from thermal inertia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2006) used the ST at a depth of 0.8m in China from 1954 to 2001, found that the variation trends of ST in different regions were different. Bai et al (2020) pointed out that the previous division of ST was mostly based on administrative and mechanical grid, but changes in ST have potential effects on vegetation growth, so ST division based on vegetation area is very meaningful. Research shows that the spatial distribution of shallow ST in China varies greatly during plant growth seasons.…”
Section: The Work Ofmentioning
confidence: 99%
“…Refs. [ 4 , 5 , 6 , 7 , 8 , 9 ] explored the relationship between NDVI and climate influences such as climate temperature and rainfall. Some studies found that the normalized NDVI has some correlation with soil moisture [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%